2016
DOI: 10.17796/1053-4628-40.3.221
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Air Drying and Magnification Methods for Detecting Initial Caries on Occlusal Surfaces Using Three Different Diagnostic Aids

Abstract: Objective-The aim of this study was to assess the effect of magnification and air-drying on detection of carious lesion. Study Design-44 human extracted premolars were selected with sound occlusal surfaces without frank cavitation. The Diagnostic techniques used were Unaided visual examination, Magnifying Loupes (4.2×) and Stereomicroscope (10×, before and after air-drying) and then the teeth were sectioned bucco-lingually and both the surfaces were examined under Stereomicroscope (50×) to assess the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Similar results were obtained by Goel et al in an in vitro study reporting 97.2% sensitivity of magnifying loupes when used in dry conditions while that with naked eye was 66.7%. 5 Pinelli et al reported similar results and observed that air drying the tooth surface before examination increases the reproducibility of caries detection rate using diagnodent. 11 Erten et al evaluated the efficiency of unaided visual examination, operating microscope and intraoral camera in the detection of dental caries and concluded that operating microscope improved caries detection as compared to visual examination alone.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Similar results were obtained by Goel et al in an in vitro study reporting 97.2% sensitivity of magnifying loupes when used in dry conditions while that with naked eye was 66.7%. 5 Pinelli et al reported similar results and observed that air drying the tooth surface before examination increases the reproducibility of caries detection rate using diagnodent. 11 Erten et al evaluated the efficiency of unaided visual examination, operating microscope and intraoral camera in the detection of dental caries and concluded that operating microscope improved caries detection as compared to visual examination alone.…”
Section: Discussionmentioning
confidence: 64%
“…4 Magnifying loupes used in a dental setup when used in dry conditions provide better specificity in the detection of early carious lesions. 5…”
Section: Introductionmentioning
confidence: 99%
“…Goel et al [ 14 ] examined the effect of magnification on the diagnosis of caries lesions in 44 extracted premolar teeth with intact occlusal surfaces and no visible cavitation. Diagnosis was made by visual inspection without magnification (unaided), ×4.2 magnification loupes, and a ×10 magnification microscope.…”
Section: Discussionmentioning
confidence: 99%